CSR and firm risk: Is shareholder activism a double-edged sword? - Konstantinos Bozos; Timothy King; Dimitrios Koutmos (Journal of Risk and Financial Management, 2022)
Few can argue with the notion that corporations should at least consider corporate social responsibility (CSR) to better understand the impact of their operations on society. However, recent empirical tests suggest CSR has an ambiguous impact on firm performance. To shed new light on this debate, we examine the extent to which voting support for nonbinding shareholder-initiated CSR proposals is empirically linked to changes in firms' underlying systematic risks. Using a rich dataset of proposals in the US from 1998 to 2011, we contribute several novel findings. First, we show that shareholder voting support is nonlinearly linked to changes in systematic risk. Specifically, proposals with low voting support increase risk while those with high support decrease risk. This nonlinearity is particularly pronounced for consumer-sensitive firms that cater primarily to individual consumers rather than for firms in non-consumer-sensitive industries that produce goods or services meant for industrial or governmental use. Second, the 2007-2009 financial crisis exacerbated increases in firms' systematic risks for proposals with low voting support. Our results, which highlight asymmetry regarding firms' CSR initiatives, remain robust when controlling for firm-specific factors as well as shifts in investor sentiment. From a risk management perspective, our findings suggest that CSR initiatives need strong shareholder support to realize benefits from the so-called 'risk-reduction hypothesis'.
Keywords: G32; G34; M14; 650; corporate social responsibility; nonbinding voting; shareholder activism; systematic risk